0107 Everyday Daytime Executive Functions in Adolescents with Insomnia. (25th May 2022) - Gruber, Reut; Saha, Sujata; Voutou, Denise; Somerville, Gail; Panaitescu, Antonia; Boulanger, Carolynn
Abstract: Introduction: Current diagnostic criteria for insomnia require self-reported sleep difficulties along with a complaint of daytime impairment. Despite the high prevalence of insomnia in adolescents, its daytime correlates are not well characterized in this age group. Executive functions (EFs) are high-level cognitive processes that coordinate memory, attention and emotions, all of which are utilized in daily functioning. Sleep deprivation impairs performance on tasks requiring EFs.A number of studies have examined the associations between insomnia and EFs in adults, but there is a paucity of studies examining EFs in adolescents with insomnia. This limits the understanding of the nature of daytime functioning in adolescents with insomnia, and impedes efforts to examine the effectiveness of interventions aimed at alleviating the daytime impairment of adolescents with insomnia.Study Objectives: 1) To compare everyday executive functioning of otherwise healthy adolescents with insomnia and that of typically developing controls; and 2) To examine the associations between sleep and everyday EFs in otherwise healthy adolescents with insomnia. Methods: 37 boys and 59 girls aged 12–16 years (mean=13.29; SD=1.1) with no medical or psychiatric disorders were divided into three groups based on their Insomnia Severity Index score: No insomnia ISI <7; Sub-threshold insomnia 8< ISI <15; Insomnia ISI> 15. Insomnia was measured using the ISI. Everyday executive functioning was measured using the Behavior Rating Inventory of Executive Function (BRIEF). Sleep was measured using Actigraphy (AW-64 series; Mini-Mitter, Sunriver, OR, USA) and sleep logs. The parents of each participant provided information regarding his/her demographic and health status. Results: Adolescents in the Insomnia group had higher scores on the BRIEF's Metacognition Index (F(2, 94)=3.1, p<0.05) and Global Executive Composite (F(2, 94)=3.6, p<0.05) and marginally shorter actigraphic sleep duration compared to the other groups ((F(2, 94)=2.5, p<0.09]). Negative correlations were found between actigraphic sleep duration and scores on the BRIEF's Behavioral Regulation Index, Metacognition Index, and Global Executive Composite [r(81)= -0.35 p<.001 r(81)= -0.49 p<.001 r(81)= -0.42 p<.001, respectively] and between sleep efficiency and the Metacognition Index [r(81)= -0.23 p<.05]. Conclusion: ConclusionInsomnia in adolescents is associated with poor EFs.LimitationThe cross-sectional nature of the study means that the association between insomnia and EFs could be bidirectional. Support (If Any): CIHR 418638 to Reut GruberRGPIN-2015-04467 to Reut Gruber